Optimization of a Resistive Capacitive Feedback Trans-impedance Amplifier Using IPSO Algorithm - Naderbeigi,; Soltani, Mohamadreza; Chaharmahali, Iman (International Journal of Computer Sciences and Engineering, 2025)
A novel low noise trans-impedance amplifier is proposed using low cost 0.18 µm CMOS technology. A resistive-capacitive feedback is used to extend the bandwidth of the amplifier. As the structure is inductor less, it is suitable for low cost integrated optical interconnects. In this paper Improved Particle Swarm Optimization have applied to determine optimal trans-resistance and noise of proposed structure of amplifier. Simulation results showed a -3 dB bandwidth of 5 GHZ with a trans-impedance gain of ≈ 62 dB ohms. The total voltage source power dissipation is less than 5 mW that is much less than that of conventional trans-impedances. The output noise voltage spectral density is 9.5 nV/sqrt(Hz) with a peak of 15nV/sqrt(Hz), while, the input referred noise current spectral density is below 10pA/sqrt(Hz) within the amplifier frequency band.